2014
DOI: 10.1063/1.4895796
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the hydrogen-bonding strength of internal water molecules and cysteine residues in the conductive state of channelrhodopsin-1

Abstract: Water plays an essential role in the structure and function of proteins, particularly in the less understood class of membrane proteins. As the first of its kind, channelrhodopsin is a light-gated cation channel and paved the way for the new and vibrant field of optogenetics, where nerve cells are activated by light. Still, the molecular mechanism of channelrhodopsin is not understood. Here, we applied time-resolved FT-IR difference spectroscopy to channelrhodopsin-1 from Chlamydomonas augustae. It is shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 107 publications
(133 reference statements)
4
63
0
Order By: Relevance
“…3). Although not identical, these spectra are also similar to recently reported FTIR difference spectra recorded at room temperature of CaChR1 in detergent micelles (25,26).…”
Section: Ftir Difference Spectroscopy Of the Cachr1 3 P 2 380 Transitionsupporting
confidence: 72%
“…3). Although not identical, these spectra are also similar to recently reported FTIR difference spectra recorded at room temperature of CaChR1 in detergent micelles (25,26).…”
Section: Ftir Difference Spectroscopy Of the Cachr1 3 P 2 380 Transitionsupporting
confidence: 72%
“…This view is common for Cr CCR2 [23,24,29], the most studied ChR. In contrast, a smaller change of amide-I was reported for Ca CCR1 at 80 K [33], and a time-resolved FTIR study of Ca CCR1 reported large changes of amide-I occurring in later intermediates [32]. Thus, limited protein structural changes to Gt CCR4 upon retinal photoisomerization are similar to Ca CCR1, but not to Cr CCR2.…”
Section: Resultsmentioning
confidence: 96%
“…For example, extensive time-resolved visible and FTIR difference studies have been performed on BR 42 and more recently Cr ChR2. 8,33,4349 In one study, time-resolved FTIR and UV–vis difference spectroscopy combined with MSD calculation led to the proposal that a downward movement of Glu90 (homologue of Glu68 in Gt ACR1) causes helix 2 to tilt downward, thereby resulting in channel opening. 44 …”
Section: Discussionmentioning
confidence: 99%